PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 8 PADANG - Apriani, Cindya; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this study is three, namely, first, describing the writing skills of the fable text of class VII students of SMP Negeri 8 Padang before using based on CIRC models. Second, describe the writing skills of the fable text of grade VII students at SMP Negeri 8 Padang after using based on CIRC models. Third, describing the effect of based on CIRC models on the writing skills of the fable text in grade VII students at SMP Negeri 8 Padang. There are two data of this study, namely the score of the results of the test writing skills in the fable text of the seventh grade students of SMP Negeri 8 before and after using the based on CIRC models. Based on the results of the study, it was concluded three things, namely first, the writing skills of the fable text of class VII SMP Negeri 8 Padang before using the based CIRC models in the Enough qualifications (C) with an average value of 64,38. Second, the report writing skills of the fable results of the seventh grade students of SMP Negeri 8 Padang after using the based on the CIRC models in the Good qualifications (B) with an average value of 83,60. Third, there is a significant effect in the use of based on the CIRC models on the report writing skills of the fable text results of class VII students at SMP Negeri 8 Padang because of the tcount> ttable (7.63 > 1.70).Â Kata Kunci: Pengaruh, Model Cooperative Integrated Reading and Composition, Fabel